Penerapan Problem Baseed Learning dengan Media Papan Pecahan dalam Meningkatkan Hasil Pembelajaran Matematika Kelas IV SD - Ardhya Pramesti; Farra Putri; Arlinda Bayu Prastiwi; Maulana Zamzuri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: Application of Baseed Learning Problems with Fractional Board Media in Improving Mathematics Learning Outcomes in Grade IV Elementary School. The research aims to increase the interest and learning outcomes of students in high-grade Mathematics learning content, namely in grade IV SDN Podorejo 01 for the 2022/2023 school year which uses concrete media assisted by the Problem Based Learning (PBL) learning model, while the concrete media used is in the form of Fraction Boards. The research subjects used were all students of class IV (Four) which contained 16 students, and consisted of 8 male students as well as 8 female students. The results of the research conducted show that this learning model with Problem Based Learning can improve the ability of students to solve problems experienced and can improve students' abilities in Fractional material. The results of this study show that learning mathematics with the PBL model with fractional board media can help students in learning mathematics, in fractional material for grade IV students of SDN Podorejo 01, School Year 2022/2023.